POSITIVE RELIGIOUS COPING SEBAGAI MODERATOR: PENGARUH ACADEMIC STRESS TERHADAP STUDENT SUBJECTIVE WELL-BEING PADA SISWA SMA BOARDING SCHOOL - Istiatun Nur Laela; Tri Na'imah; Herdian; Imam Faisal Hamzah (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aimed to analyze the influence of academic stress on student subjective well-being and to examine the role of positive religious coping as a moderating variable among high school students in a boarding school setting. The study employed a quantitative approach with an explanatory research design. The research population consisted of all students of SMA IMBS Yogyakarta who resided in the dormitory, totaling 139 students, and a saturated sampling technique was used. Data were collected using a questionnaire with a five-point Likert scale. The instruments were adapted from the Educational Stress Scale for Adolescents (ESSA), Student Subjective Well-Being Questionnaire (SSWBQ), and Brief RCOPE. Data analysis was conducted using SEM-PLS with the assistance of SmartPLS 4. The results showed that academic stress had a negative and significant effect on student subjective well-being (β = −0.436; p < 0.05). Positive religious coping had a positive and significant effect on student subjective well-being (β = 0.536; p < 0.05). However, positive religious coping did not function as a moderating variable in the relationship between academic stress and student subjective well-being (β = −0.095; p > 0.05). These findings indicate that higher levels of academic stress experienced by students are associated with lower levels of student subjective well-being. Meanwhile, positive religious coping can enhance student subjective well-being, but it does not strengthen or weaken the influence of academic stress on student subjective well-being.